The structure and function of the epidermal barrier in patients with atopic dermatitis – treatment options. Part two - Pelc, Jagoda; Czarnecka-Operacz, Magdalena; Adamski, Zygmunt (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Atopic dermatitis (AD) is a chronic and recurrent disease induced by underlying defects of the epidermal barrier and immunological disorders, typical of atopic diseases. The genetic and immunological mechanisms (outlined in the previous paper) affecting the dysfunction of the barrier are intensified by environmental factors, e.g. airborne and food allergens, infections and stress. For this reason, proper skin care, which prevents further damage and restores the epidermal barrier is of such importance in the field of AD therapy. Appropriate therapy is based on emollients which, coupled with anti-inflammatory and antipruritic treatment, should be used as the first-line therapy. The aim of the present paper is to outline the effects of the abovementioned factors on the dysfunction of the epidermal barrier as well as to emphasize the importance of proper atopic skin care in maintaining the integrity of the barrier and preventing exacerbation of the disease.